2003
DOI: 10.1046/j.1468-1331.2003.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Human African trypanosomiasis: quantitative and qualitative assessment of intrathecal immune response

Abstract: Quantitative and qualitative techniques for assessment of the intrathecal humoral immune response in human African trypanosomiasis were compared, and their diagnostic potential for detection of the meningo-encephalitic stage of the disease was evaluated. Total and trypanosome specific immunoglobulin G (IgG) and IgM intrathecal synthesis were studied in paired cerebrospinal fluid (CSF) and blood samples of 38 trypanosomiasis patients and in three controls using Reiber's formulae. The presence of CSF-specific ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The origin and composition of the CSF immunoglobulins have been recently studied in experiments with large patients groups. As previously suspected (36), these studies confirmed that the elevated immunoglobulin concentration in the CSF is due to intrathecal synthesis and that the dominant IgM presence was an early marker of CNS invasion whereas blood-CSF barrier dysfunction was found late in the course of CNS involvement (13,65). These results were further confirmed by studies of 272 HAT patients from different areas of endemic infection, where intrathecal synthesis of IgM was found in 95% of patients with second-stage illness (63).…”
Section: Stage Determination: Cerebrospinal Fluid Examinationsupporting
confidence: 84%
“…The origin and composition of the CSF immunoglobulins have been recently studied in experiments with large patients groups. As previously suspected (36), these studies confirmed that the elevated immunoglobulin concentration in the CSF is due to intrathecal synthesis and that the dominant IgM presence was an early marker of CNS invasion whereas blood-CSF barrier dysfunction was found late in the course of CNS involvement (13,65). These results were further confirmed by studies of 272 HAT patients from different areas of endemic infection, where intrathecal synthesis of IgM was found in 95% of patients with second-stage illness (63).…”
Section: Stage Determination: Cerebrospinal Fluid Examinationsupporting
confidence: 84%
“…By contrast, increased IgM concentrations in CSF, caused by synthesis within the spinal cord, are an early and specifi c marker of CNS invasion. [103][104][105] A fi eld-designed latex agglutination test for IgM in CSF has shown promising results, but needs further validation. 106 Antibodies against neurofi laments, galactocerebrosides, neurofi laments, and glial fi brillary acidic proteins are also promising CSF markers of second-stage disease.…”
Section: Diagnosismentioning
confidence: 99%
“…Some authors have reported that early stage patients who demonstrated detectable levels of intrathecally synthesized Ig did not relapse after 12 months of follow-up and this in both chronic and acute forms of the disease. 15,41 This suggests that intrathecal Ig synthesis, though not a specific or sensitive parameter for identification of late stage disease, may be interesting as a potential marker of early stage HAT. It has also been shown that a combination of CSF CXCL10, lipocalin 2 and secretory leucocyte peptidase inhibitor (SLPI) protein levels correlated with late stage HAT (as defined by the WHO criteria) compared with early stage disease in patients from Malawi and the Democratic Republic of Congo.…”
Section: The Problem Of Disease Staging In Hatmentioning
confidence: 99%